(untitled) (The Peerian Journal, 2023)
Creating an ideal microclimate ithin greenhouses is crucial for successful plant growth and maximizing crop yield. Temperature control plays a vital role in maintaining optimal conditions throughout the growing season. Perforated air pipe systems offer a innovation by distributing hot air uniformly, resulting an optimized microclimate. This article explores the benefits and functionality of using perforated air pipes to create an optimal microclimate in greenhouses.